2021
DOI: 10.1007/s13239-021-00577-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Modular Hemodynamic Simulator for Accurate In Vitro Simulation of Physiological and Pathological Pressure Waveforms in Native and Bioartificial Blood Vessels

Abstract: Purpose In vitro stimulation of native and bioartificial vessels in perfusable systems simulating natural mechanical environments of the human vasculature represents an emerging approach in cardiovascular research. Promising results have been achieved for applications in both regenerative medicine and etiopathogenetic investigations. However, accurate and reliable simulation of the wide variety of physiological and pathological pressure environments observed in different vessels still remains an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These free‐standing segments are needed to enable easy and quick vascular anastomoses in the potential target organism. Therefore, fibrin grafts have been shown to be of sufficient mechanical strength to withstand physiological and supraphysiological pressures even without structural support of surrounding tissue (Helms, Haverich, et al, 2021; Helms, Lau, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These free‐standing segments are needed to enable easy and quick vascular anastomoses in the potential target organism. Therefore, fibrin grafts have been shown to be of sufficient mechanical strength to withstand physiological and supraphysiological pressures even without structural support of surrounding tissue (Helms, Haverich, et al, 2021; Helms, Lau, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the integration of the desired cell types (i.e., pancreatic β‐cells, smooth muscle cells, and hepatocytes), the matrix can be useful in various fields of organ engineering. Nonetheless, future studies are needed to verify seeding capacity for different cell types, generate a hierarchically organized interconnection between microchannels and capillary‐like tubes and to assess the performance of the patch after implantation in vivo (Helms, Haverich, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile circulation was controlled with a left ventricular model, and the system allowed the control of dynamic flow, pressure waveforms, heart rate, and systolic fraction to match the physiological conditions of fetal or adult arteries or veins (220). Helms et al developed a modular hemodynamic simulator which allowed the exposure of fibrin blood vessels to site specific pressure curves, and allowed the simulation of physiological and pathological pressure conditions for small caliber vessels (213).…”
Section: Dynamic Culture Conditionsmentioning
confidence: 99%
“…This demonstrated that the elimination of the anesthesia step, which is essential in animal studies, allows for a more accurate hemodynamically-equivalent model. Modular hemodynamic simulator which allowed the exposure of fibrin blood vessels to site specific pressure curves, and allowed the simulation of physiological and pathological pressure conditions for small caliber vessels (213) (191). The endothelium layer was stimulated with TNF-α or LDL and monocytes were then perfused into the system.…”
Section: Dynamic Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation